Role of glutamate in the development of visual pathways - Majumdar, Sriparna (Frontiers in Ophthalmology, 2023)
Glutamate is an important amino acid, metabolite and excitatory neurotransmitter, which is found in its free form in the extracellular spaces of the central nervous system (CNS). More than half of all synapses in the CNS release glutamate. It is the main neurotransmitter driving the light responses in the retina. All types of photoreceptors, bipolar, ganglion and one type of glycinergic amacrine cells express specific subtypes of vesicular glutamate transporters and are the main source of endogenous glutamate in the retina besides Müller glia that are responsible for glutamate homeostasis, release and reuptake. Reduced or excessive extracellular glutamate was detected in the synaptic clefts of several naturally occurring or transgenic eye disease models, in which network rewiring and altered functions were observed. These led to the hypothesis that glutamate is one of the extrinsic signals for visual pathway development. This minireview examines the anatomical and physiological evidences supporting, or refuting, the influence of glutamate on retinal neurogenesis, axon guidance, programmed cell death, synapse formation and network maturation.